Cyclin A triggers Mitosis either via the Greatwall kinase pathway or Cyclin B. (30th April 2020) - Hégarat, Nadia; Crncec, Adrijana; Suarez Peredo Rodriguez, Maria F; Echegaray Iturra, Fabio; Gu, Yan; Busby, Oliver; Lang, Paul F; Barr, Alexis R; Bakal, Chris; Kanemaki, Masato T; Lamond, Angus I; Novak, Bela; et al.
Abstract: Two mitotic cyclin types, cyclin A and B, exist in higher eukaryotes, but their specialised functions in mitosis are incompletely understood. Using degron tags for rapid inducible protein removal, we analyse how acute depletion of these proteins affects mitosis. Loss of cyclin A in G2‐phase prevents mitotic entry. Cells lacking cyclin B can enter mitosis and phosphorylate most mitotic proteins, because of parallel PP2A:B55 phosphatase inactivation by Greatwall kinase. The final barrier to mitotic establishment corresponds to nuclear envelope breakdown, which requires a decisive shift in the balance of cyclin‐dependent kinase Cdk1 and PP2A:B55 activity. Beyond this point, cyclin B/Cdk1 is essential for phosphorylation of a distinct subset of mitotic Cdk1 substrates that are essential to complete cell division. Our results identify how cyclin A, cyclin B and Greatwall kinase coordinate mitotic progression by increasing levels of Cdk1‐dependent substrate phosphorylation. Synopsis: The specific functions of mitotic CDK1‐activating cyclins A and B in higher eukaryotes have remained unclear. Acute depletion studies combined with phosphoproteomics and computation modeling now define their exact roles and interplay with other pathways during initiation, progression and completion of mammalian cell division. A novel degron‐tagging strategy in RPE‐1 cells reveals how acute loss of either cyclin A or B affects mitosis. Cyclin A is critical to trigger the feedback loops involved in initial Cdk1 activation. Cyclin B is not required for mitotic entry, but essential for phosphorylation of specific Cdk1 substrates, and for sister chromatid segregation and cytokinesis. Mitotic cells buffer loss of Cyclin B by inhibition of PP2A:B55 phosphatase via the Greatwall kinase pathway. Abstract : Acute degron‐mediated depletion defines the exact roles of mitotic cyclins and related CDK1 substrate phosphorylation during initiation, progression and completion of mammalian cell division.